Intercultural Language Teaching in EFL Contexts: Principles, Interventions, Approaches and Future Directions - Zhou, Jingjing; Florence Gilliam, Kayad; Vimala, Govindaraju (Woody International Publish Limited, 2025)
This paper examines Intercultural Language Teaching (ICLT) in EFL contexts, focusing on its theoretical links between language and culture, core principles, effective interventions, and existing challenges. It reveals insufficient ICLT implementation due to traditional pedagogies, gaps in teacher practice and qualitative research. Implications for research and practice are proposed to enhance learners’ intercultural communicative competence (ICC).